Effect of using the additional field player on attack efficiency during 2017 Women's Handball World Championship - Krahenbühl, T.; Pereira, L. L. L.; Menezes, R. P.; Amazonas, S. M. F.; Leonardo, L. (Acta Gymnica, 2021)
Background: Rule changes such as the use of the additional field player in the attack to replace the goalkeeper can significantly change the tactical strategies of the handball game.